Comparison of Efficacy of Beractant and Poractant Treatment Performed with Minimal Invasive Technique - Selahattin Akar; Sevilay Topcuoglu; Emre Dincer; Elif Ozalkaya; Guner Karatekin; Tulin Gokmen Yildirim (Iranian Journal of Neonatology, 2021)
Background: The literature review has demonstrated the short-term benefits of minimally invasive surfactant therapy (MIST) in spontaneously breathing preterm neonates. This study was conducted to compare the efficacy of beractant and poractant alfa treatments performed with the MIST method in newborns with respiratory distress syndrome (RDS) and its effect on preterm morbidity and mortality. Methods: The patients diagnosed with RDS less than 35 weeks of gestational age and stabilized with nasal continuous positive airway pressure (nCPAP) in the delivery room were screened retrospectively. The cases were divided into two groups of beractant (BG) and poractant alfa (PG). While the BG (n=24) consisted of patients receiving beractant treatment with MIST during nCPAP, the PG (n=34) were those subjected to poractant alfa treatment. Results: It was found out that in PG the scores of surfactant reflux to esophagus and desaturation during surfactant administration were significantly lower (P=0.012 and P=0.009, respectively). No significant difference was observed between the two groups regarding bronchopulmonary dysplasia, sepsis, patent ductus arteriosus, pneumothorax, intubation rate in postnatal 72 h, total period of intubation, nCPAP, duration of hospitalization, and mortality rate. Conclusion: According to the results of this study, surfactant reflux to esophagus and desaturation during the intervention procedure were lower in the PG group, most probably due to a lower volume of poractant than beractant. However, since a small number of patients were included in this study, it is recommended to perform further studies consisting of a larger number of cases.